(3eYGde GdJfRjds - (3CMeO Hf jhSa Hf eSYhO GdaQGA GdHZhj GdMdHjs
(3ChdgG (B:s
(3cgjYU bQC CHh YeQh s
(3BNQgG (B:s
(3Je cJGH eYGde GdJfRjd s
(3YdjgG Jedc GdMGL eMeO Hf GdMGL eUWai GdeZQHis
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1726s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JaSjQ (B216) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs